IMPROVING STUDENTS' ABILITY TO STORY YOUR EXPERIENCES WITH THE TALKING STICK MODEL IN CLASS I I I STUDENTS AT SDN 1 3 KABILA BONE BOLANGO DISTRICT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The formulation of the problem in this study is "Can the ability of students to share their experiences in class III at SDN Kabila, Bone Bolango Regency , improve?". The purpose of this study was to "Improve students' ability to tell experiences with the Talking Stick model in class III at SDN 13 Kabila, Bone Bolango Regency". The model used in this research is a class action approach. This study uses data collection techniques through observation, testing and documentation. The subjects of this study were 21 class III students. The results of this study indicate that students who have the ability to tell experiences using the Talking Stick model in cycle I meeting 1 are 5 students with a percentage of 24%, in cycle I meeting 2 there are 9 students with a percentage of 43%. While the results in cycle II meeting 1 were 13 students with a percentage of 62%, in cycle II meeting 2 there were 18 students with a percentage of 86%. The results in cycle II have reached the indicators of success that have been set, so it can be concluded that by using the Talking Stick model the ability of students to share their experiences in class III SDN 13 Kabila, Bone Bolango Regency has increased.